COMPUTER SIMULATION IN MECHANICS TEACHING AND LEARNING: A CASE STUDY ON STUDENTS UNDERSTANDING OF FORCE AND MOTION - Sari, Dyah Permata; Madlazim, M (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2015)
The objective of this research was to develop a force and motion simulation based on the open-source Easy Java Simulation. The process of computer simulation development was done following the ADDIE model. Based on the Analysis and Design phases, the Development phase used the open-source Easy Java Simulation (EJS) to develop a computer simulation with physics content that was relevant to the subtopic. Computing and communication technology continue to make an increasing impact on all aspects of education. EJS is a powerful didactic resource that gives us the ability to focus our students attention on the principles of physics. Using EJS, a computer simulation was created through which the motion of a particle under the action of a specific force can be studied. The implementation phase is implemented the computer simulation in the teaching and learning process. To describe the improvements in the students understanding of the force and motion concepts, we used a t-test to evaluate each of the four phases. These results indicated that the use of the computer simulation could improve students force and motion conceptual competence regarding Newton’s second law of motion.